2007
DOI: 10.1192/pb.bp.106.012815
|View full text |Cite
|
Sign up to set email alerts
|

Violence against psychiatrists by patients: survey in a London mental health trust

Abstract: Aims and MethodA survey was undertaken to investigate assaults of psychiatrists by patients in a 12-month period. Surveys were sent to 199 psychiatrists representing all sub-specialties and grades in a London mental health trust.ResultsThere were 129 returned responses (response rate 64.8%). In the 12-month study period, 12.4% of all psychiatrists and 32.4% of senior house officers were assaulted. None received or took up offers of formal, as opposed to informal, psychological support. Most assaults occurred o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 5 publications
(9 reference statements)
2
18
0
Order By: Relevance
“…The questionnaires were developed according to the method used by previous investigators. 1,3 Physical assaults were defined as actual physical attacks (e.g. hit, struck with an object, shaken, pushed, attempted strangling, attempted rape, kicking, biting) and not threats or verbal aggression.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaires were developed according to the method used by previous investigators. 1,3 Physical assaults were defined as actual physical attacks (e.g. hit, struck with an object, shaken, pushed, attempted strangling, attempted rape, kicking, biting) and not threats or verbal aggression.…”
Section: Methodsmentioning
confidence: 99%
“…Demographic data such as gender, age, marital status and duration of employment were also obtained. Attitude of staff towards physical assaults by patients was investigated using the four attitude items from Dhumad et al 1 All replies were anonymous.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies aiming description of violence exposure of healthcare professionals working in psychiatry departments (3,7,24,(29)(30)(31) were carried out. It is reported in studies with various rates that healthcare professionals were exposed to violence at least once within the last one year (2,3,7,14,18,32).…”
Section: Discussionmentioning
confidence: 99%
“…12 However, vulnerability to violence may not be influenced by courses on management and prevention of violence. 19 A study in Wales reported a high uptake of induction and breakaway courses by psychiatric trainees, but it also highlighted deficiencies in the physical work environment such as poor access to panic buttons, personal alarms and appropriate interview rooms. 20 Of concern is the finding that the process of audit did not lead to an improvement in the safety of interview rooms.…”
Section: Local Policies and Trainingmentioning
confidence: 99%